2005
DOI: 10.1103/physrevd.72.095005
|View full text |Cite
|
Sign up to set email alerts
|

Full one-loop supersymmetric corrections to charged Higgs boson pair production inγγcollisions

Abstract: The complete one-loop electroweak corrections to charged Higgs boson pair production in γγ collision mode at linear colliders in the minimal supersymmetric standard model (MSSM), are calculated in this paper. We discuss the dependence of the corrections to the subprocess γγ → H + H − on the related parameters, such as the colliding energy, charged Higgs boson mass M H ± and some supersymmetric parameters tan β, M SUSY and gaugino mass parameter M 2 . We find that the corrections generally reduce the Born cross… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…[16]. The in-house 2 → 4 phase-space integration routine was also once verified in our previous work [27].…”
Section: Checksmentioning
confidence: 93%
See 2 more Smart Citations
“…[16]. The in-house 2 → 4 phase-space integration routine was also once verified in our previous work [27].…”
Section: Checksmentioning
confidence: 93%
“…The subroutines for one-loop integrals with complex masses are coded based on the LoopTools2.1 [20] package which comes from FF library [25]. The 2 → 4 phase-space integration routine [27] is created based on the 2to3.F program in FormCalc4.1 package. The five-body phase-space integration for hard gluon radiation process e + e − → W + W − b b g is accomplished by using CompHEP-4.4p3 program [26].…”
Section: Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, the process was handled in Ref. [19] including the real radiative corrections. The calculation was presented for various benchmark points in MSSM, and the results showed that the correction is overall between -60% to +5% at √ s = 1 TeV.…”
Section: Introductionmentioning
confidence: 99%
“…The charged Higgs boson pair production in the γγ → H + H − mode was considered in [23][24][25]. In general, the higher-order corrections to the γγ → H + H − subprocess decrease the tree-level total cross section by about a few percent; see [26,27]. Also the associated production γγ → H ± W ∓ was discussed in the literature [28].…”
Section: Introductionmentioning
confidence: 99%